Oscillator strength measurements of the 4s5s 3S1 → 4snp 3Po2 Rydberg transitions of zinc. Issue 2 (7th February 2019) - Aisha, Ghulam; Shah, Mehmood; Nadeem, Ali; Haq, Sami-Ul; Shahzada, Shaista
Abstract: In the present experimental work, oscillator strengths of the 4s5s 3 S1 → 4s n p 3 P o 2 (18 ≤ n ≤ 53) Rydberg transitions of zinc are reported. The stepwise laser excitation from the ground state 4s 2 1 S0 was achieved using three dye laser beams simultaneously pumped by the second (532 nm) and third (355 nm) harmonics of a Q-switched Nd: YAG (Neodymium-doped yttrium aluminum garnet) laser. The vapor containment and detection system was a single wire thermionic diode ion detector operating in space charge limited mode. A trend of the above-mentioned f -values from n = 18 to 53 versus the principle quantum number n has been presented. Furthermore, continuity has been verified between the discrete f -values and the oscillator strength density at the threshold.